Evaluation of Clinical Outcome in Traumatic Facial Nerve Paralysis - Shankar, Abhijit; George, Shibu; Somaraj, Satheesh (International Archives of Otorhinolaryngology, 2021)
Introduction The facial nerve is the most commonly paralyzed nerve in the human body, resulting in far-reaching functional, aesthetic and emotional concerns to the patient.Objective Evaluation of the clinical outcome of 47 patients with traumatic facial nerve paralyses, with respect to clinical recovery and audiological sequelae.Methods A descriptive longitudinal study was conducted over 24 months between January 2017 and December 2018 at a tertiary center with detailed clinical, topodiagnostic, audiometric and radiological evaluation and regular follow-up after discharge.Results Road traffic accidents constituted 82.98% of the trauma cases, out of which 76.60% were found to be under the influence of alcohol.Delayed facial paralysis was observed in 76.60% cases. Temporal bone fracture was reported in 89.36%, with otic capsule (OC) sparing fractures forming 91.49% of the cases. Topologically, the injury was mostly at the suprachordal region around the second genu. The majority of the patients (65%) attained full recovery of facial nerve function with conservative medical management. Audiometrically, 77.27% of the patients had hearing loss at the time of presentation, of which 64.71% were conductive in nature; 51.22% attained normal hearing at follow-up visits.Conclusion Early initiation of steroid therapy, concurrent eye care and physiotherapy are the cornerstones in the management of traumatic facial nerve paralysis.
Keywords: facial nerve; facial paralysis; temporal bone; logistic regression